Implementasi Program Inovasi : Jalak Wadul Mas untuk Meningkatkan Kesejahteraan Penyandang Masalah Kesejahteraan Sosial di jawa Timur - Vincentius Gerald B. P; Ulul Albab; Kristyan Kristyan (RISOMA : Jurnal Riset Sosial Humaniora dan Pendidikan, 2026)
This research aims to analyze the implementation of the "Jalak Wadul Mas" (Jawa Timur Layanan Pengaduan Warga dan Dukungan Masyarakat/East Java Citizen Complaint Service and Community Support) innovation program in improving the welfare of people with social welfare problems (PMKS) in East Java Province. The Social Service of East Java Province developed this program as an integrated digital platform for complaint handling, social assistance distribution, and empowerment of vulnerable groups. Using the policy implementation theory from Edward III, this study examines four critical factors: communication, resources, disposition, and bureaucratic structure. This qualitative research employs a descriptive approach, with data collected through in-depth interviews, observation, and documentation at the Social Service of East Java Province during June-August 2025. Informants include program managers, field social workers, PMKS beneficiaries, and community stakeholders. The results indicate that the Jalak Wadul Mas program has successfully served 45,678 PMKS across 38 districts/cities in East Java, with a 78% complaint resolution rate and average response time of 3 working days. The program integrates multiple services, including emergency assistance, rehabilitation referrals, skills training, and economic empowerment. Key success factors include strong leadership commitment, adequate technology infrastructure, and collaborative networks with community organizations. Challenges remain in human resource capacity, internet connectivity in remote areas, and cross-sectoral coordination. This study recommends strengthening digital literacy training for beneficiaries, expanding mobile service units, developing real-time monitoring dashboards, and establishing sustainable funding mechanisms.